Implementing TQM in Islamic Education: A Phenomenological Study of Management Practice at MTs Darul Amin Palangka Raya - Rahmat Fauzi; Achmad Robita; Muhammad Noor; Achmad Junaidi; Dedy Irawan; Moc Chotib; Ahmadi (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2025)
This study aims to explore the development of a Total Quality Management (TQM)-based management model at MTs Darul Amin Palangka Raya through the lived experiences of stakeholders. Using a qualitative phenomenological approach, the research delves into how teachers, administrators, and parents perceive, interpret, and enact TQM within an Islamic educational framework. Data were collected through in-depth interviews with 15 informants, participatory observation, and documentation analysis over six months, with attention to the essence of their subjective experiences. The findings reveal that the implementation of the TQM model at MTs Darul Amin Palangka Raya is influenced by five key dimensions: transformative leadership, stakeholder engagement, continuous improvement, data-driven decision making, and integration of Islamic values in management. Participants described these dimensions not merely as managerial tools but as meaningful practices tied to Islamic concepts like amanah (trustworthiness) and itqan (excellence). Challenges such as resistance to change and resource limitations emerged as shared lived realities among stakeholders. The study culminates in an